Rural conceptions of queer-intended space and place: the physical, virtual, and relational structures of Grindr and SCRUFF - Nelson, Mark (Kansas State University, 2019)
Discussions of space and place are essential to many researchers who assert that space and place are integral in shaping how individuals experience the social world. In early work, space was often treated as a physical location without connections to or for human actors, and place is defined as a location that does have connections to, or is for, human actors (Cloke et al 1991; Seamon & Sowers 2008; Selten & van der Zandt; Tuan 1977). Understandings of space and place have expanded past a singular definition regarding the physical to include cyberspace- a virtual space and place. Furthermore, scholarship in queer geography has indicated that queerness provides important insights into how people experience and create space and place. My study examines the question: How do rural users of queer-intended location based social networking (LBSN) apps conceptualize space and place? I interviewed 11 rural users of the apps Grindr and SCRUFF. I used a phenomenological approach with semi-structured interviews conducted over the messaging functions of the apps. I asked 5 general and cryptic questions regarding space and place to see how users would interpret them. I then followed their narratives to understand their conceptions of space and place; many of which I did not anticipate. My following thesis is a full report of the results garnered with my study. Ultimately, this study shows that allowing, potentially, queer folx to identify their own conceptions of space and place shows richer conceptions of space and place than have been identified in previous literature. Space and place take on various connotations respective to the user, and rural users of these queer-intended LBSN apps discuss how Grindr and SCRUFF are spaces and places that serve different users and have contingency to physical geography.
Keywords: Queer Geography; Queer Studies; Location Based Social Networking (LBSN); Phenomenology; Rural Sociology